PEMODELAN SEBARAN TOTAL SUSPENDED SOLID (TSS) DARI PEMBUANGAN LIMBAH PENGEBORAN DI LAUT NATUNA UTARA - Ari Gunawan Wardhana; Santoso (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2023)
Dumping of drilling waste (cutting and used drilling mud) into the sea is predicted to have an impact on sea waters. To predict the distribution of waste in sea waters, a simulation model of the distribution of waste is carried out with the main parameter is Total Suspended Solid (TSS). The source of data for modelling comes from the drilling activities of oil and gas companies in the North Natuna Sea. The model results show an increase in the maximum TSS concentration due to the highest dumping of drilling mud around 60-65 mg/l which occurred in the Transitional Season II during section-1 drilling. Meanwhile, the increase in TSS concentration due to drill cuttings was highest around 5-6 mg/l in the West Season during section-2 drilling. When compared with the seawater TSS quality standard according to PP No. 22 of 2021 Appendix VIII for marine biota (20 mg/l), the TSS concentration due to drilling mud discharge appears to exceed the quality standard at a radius of 50 m from the discharge point, whereas due to drill cutting dumping it is not seen that anything exceeds the quality standard from a radius of 50 m to 500 m from the discharge point. The increase in TSS concentration due to dumping of drilling mud and cuttings at 500 m from outfall in all seasons is far below the quality standard, namely from <0.02 mg/l to <2 mg/l.